Populist Communication in the Post-Truth Age: A Comparative Analysis of Treatment of Journalists by Donald Trump and Aleksandar Vučić - Kulic, Milica (Journal of Regional Security, 2020)
The populist communication model of perceiving journalists as “the enemies of the state”, presented in the political communication of the 45th US President Donald Trump, seems to be not only reserved for the US but has become a trend for populist leaders worldwide. Such rhetoric has been revitalized by the recent rise of populism in Western Europe, fostered in Central and Eastern Europe and recognized in the local media landscape in Serbia. This paper compares the communication models of US President Donald Trump and the Serbian President Aleksandar Vučić as directed toward journalists. The results show that these leaders use a similar communication pattern: they favour divisive issues, stressing a friendly vs. unpatriotic media, alienating the media outlets and contributing to the further polarisation in media and society. This research is based on a qualitative analysis of 12 press conferences, including media statements, chosen for their unique interactions with media representatives.